Nano-hydroxyapatite-evoked immune response synchronized with controllable immune adjuvant release for strengthening melanoma-specific growth inhibition. (June 2022) - Chen, Zhu; Deng, Jing; Cao, Jun; Wu, Hongfeng; Feng, Gang; Zhang, Ruolan; Ran, Bin; Hu, Kun; Cao, Huan; Zhu, Xiangdong; Zhang, Xingdong
Abstract: Concerns about the potential systematic toxicity limit the extensive application of traditional therapeutic drugs for melanoma therapy, nano-hydroxyapatite (nHA) with good biocompatibility and anti-tumor ability could be an alternative choice. In this study, nHA was employed as an anti-tumor biomaterial due to its tumor-specific toxicity. Meanwhile, granulocyte-macrophage colony-stimulating factor (GM-CSF) served as the immune adjuvant to activate the immune response. The delivery platform was fabricated by co-encapsulation of both nHA and GM-CSF into a biocompatible thermosensitive PLGA-PEG-PLGA hydrogel. The results showed that the bio-activities of nHA and GM-CSF could be well-maintained within the hydrogel. Interestingly, the addition of nHA could attenuate the burst release of GM-CSF due to possible protein absorption capacity of nHA, which is beneficial for GM-CSF sustainable release at the tumor site, achieving boosted and prolonged anti-tumor immunity. The in vitro and in vivo data demonstrated that nHA/GM-CSF hydrogel exhibited greater potency to inhibit tumor growth via enhanced CD8 + T - cell response compared with hydrogel and nHA hydrogel groups, contributed by the synergistic effects of nHA and GM-CSF. Overall, the strategy combining nHA and immune adjuvant shows great promise, which largely broadens the choice of combinational therapies for melanoma. Statement of significance: Nano-hydroxyapatite (nHA) has been confirmed to specifically inhibit melanoma tumor growth and induce immune response. However, its antitumor efficiency and immunity-evoking capacity are limited. In this study, granulocyte-macrophage colony-stimulating factor (GM-CSF) was introduced to serve as the immune adjuvant. Both of them were encapsulated into a biocompatible thermosensitive PLGA-PEG-PLGA hydrogel. The addition of nHA could attenuate the burst release of GM-CSF due to the interaction with nHA, which is beneficial for GM-CSF sustainable release at tumor site, achieving boosted and prolonged anti-tumor immunity. Anti-tumor immune response could be activated due to the release of tumor-associated antigen and tumor debris induced by the specifically tumor inhibition effect of nHA and GM-CSF. The combination of nHA and GM-CSF could play synergistic inhibiting effect on tumor growth via boosting and prolonging anti-tumor immunity. Graphical abstract: Image, graphical abstract